PEMBENTUKAN SPIRIT JIWA MUSLIMPRENEURSHIP MELALUI MATA KULIAH KEWIRAUSAHAAN BERBASIS SYARIAH - Lubis, Anggia Sari; Ovami, Debbi Chyntia (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2018)
Entrepreneurship was an important factor to increase the economic growth of our country. Muslimpreneur was an actor of entrepreneurship that have an identity with personality and characteristic as a true moslem to run their business with islamic value. The real effort that we can do is to shaping and instill principles of moslempreneur soul by entrepreneur based sharia courses. The aims of this research was to knowing how to shaped of spirit moslempreneur soul by entrepreneur based sharia courses. The research method is qualitative descriptive and the data collected by observation and interview. The result of this research is entrepreneur based sharia courses can be a framework of shaping the spirit of moslempreneur soul for students